Teaching distance improvement per stroke (DIPS): Utilising drills designed specifically to reduce strokes per length - Dodson, A. (coachesinfo.com)
The importance of distance per stroke in competitive swimming is a generally accepted principle and has been well documented. Many authors have addressed the benefits of stroke length to both speed and efficiency. Unfortunately, there has not been equivalent effort placed on how to teach to improve distance per stroke.